2010
DOI: 10.3390/molecules16010016
|View full text |Cite
|
Sign up to set email alerts
|

Novel Synthesis of Hydrazide-Hydrazone Derivatives and Their Utilization in the Synthesis of Coumarin, Pyridine, Thiazole and Thiophene Derivatives with Antitumor Activity

Abstract: The reaction of cyanoacetyl hydrazine (1) with 3-acetylpyridine (2) gave the hydrazide-hydrazone derivative 3. The latter compound undergoes a series of heterocyclization reactions to give new heterocyclic compounds. The antitumor evaluation of the newly synthesized products against three cancer cell lines, namely breast adenocarcinoma (MCF-7), non-small cell lung cancer (NCI-H460) and CNS cancer (SF-268) was performed. Most of the synthesized compounds showed high inhibitory effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(68 citation statements)
references
References 22 publications
3
64
0
Order By: Relevance
“…In Chart 1, the key intermediates (E)-N′-(3,4-disubstituted benzylidene)-2-cyanoacetohydrazide 1 and 2 were prepared by reacting cyanoacetic acid hydrazide with the appropriate substituted benzaldehyde. 48) Refluxing 1 and 2 with acetyl acetone, ethyl acetoacetate, ethyl cyanoacetate or malononitrile in absolute ethanol containing catalytic amount of piperidine afforded the targeted (E)-1-((3,4-disubstituted benzylidene) amino)-4,6- Milrinone, I 30) , II 34) , III 35) and the proposed structure modifications in the scaffold to obtain the target compounds A-C.…”
Section: Resultsmentioning
confidence: 99%
“…In Chart 1, the key intermediates (E)-N′-(3,4-disubstituted benzylidene)-2-cyanoacetohydrazide 1 and 2 were prepared by reacting cyanoacetic acid hydrazide with the appropriate substituted benzaldehyde. 48) Refluxing 1 and 2 with acetyl acetone, ethyl acetoacetate, ethyl cyanoacetate or malononitrile in absolute ethanol containing catalytic amount of piperidine afforded the targeted (E)-1-((3,4-disubstituted benzylidene) amino)-4,6- Milrinone, I 30) , II 34) , III 35) and the proposed structure modifications in the scaffold to obtain the target compounds A-C.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several publications reported that hydrazide-hydrazones are valuable intermediates in the synthesis of heterocyclic compounds with potential pharmaceutical and biological activities [4] [5]. Based on those reports and in continuation of our 1 H NMR spectrum of 5 revealed, in addition to the aromatic benzothiazole protons, two doublets at δ H 2.97 and 2.84 ppm., with J = 16 Hz, as required for the methylene protons of H-3 indicating that these protons are in a different environment.…”
Section: Introductionmentioning
confidence: 88%
“…Moreover, the reaction of 15 with salicylaldehyde (17) gave the coumarin derivative 18. Several coumarin derivatives were reported through literature using similar reaction routes [19]- [21].…”
Section: Resultsmentioning
confidence: 99%